Teachers’ Familiarity of Irlen syndrome and its relationship to their use of specialized strategies in teaching reading - Al Darmaki, Moza (Al-Adab Journal, 2025)
This study aimed to identify the extent of teachers’ Familiarity of Irlen Syndrome and its relationship to their use of specialized strategies in teaching reading. The study sample consisted of (67) male and female teachers in different educational stages. The sample included (12 males, 55 females), with an average age of 39.4, and a standard deviation of 0.87. They were selected randomly. The study used the descriptive correlational approach for its suitability to the study purposes. The study tools consisted of two questionnaires (prepared by the researchers), namely (a questionnaire measuring teachers’ knowledge of Irlen Syndrome, and a questionnaire on teachers’ use of specialized strategies in teaching reading). The results of the study regarding the questionnaire of teachers’ knowledge of Irlen syndrome showed a low level for the two dimensions (the dimension of teachers’ knowledge of Irlen syndrome, and the dimension of diagnosis and symptoms), and for the questionnaire as a whole, the value of (t) is not statistically significant, and the level is average in general. The results of the study also indicated that teachers’ use of reading difficulties strategies in general ranged between a large and very large level, and there is a direct correlation between the degree of teachers’ knowledge of Irlen syndrome and their use of reading teaching strategies with these students. There are also no statistically significant differences in the study variables attributed to the difference in the demographic variables of the sample (such as gender, age, educational stage, experience, training courses, qualification).